Changes in liver microRNA expression and their possible regulatory role in energy metabolism-related genes in hibernating black bears - Nishida, Kazuhei; Shimozuru, Michito; Okamatsu-Ogura, Yuko; Miyazaki, Mitsunori; Soma, Tsukasa; Sashika, Mariko; Tsubota, Toshio (Journal of comparative physiology. B, Biochemical, systemic, and environmental physiology, 2021)
Hibernating bears survive up to 6 months without feeding while yet maintaining metabolic homeostasis. We previously reported expression changes in energy metabolism-related genes in the liver of hibernating Japanese black bears. The present study examined the role of microRNAs in the regulation of hepatic gene expression during hibernation. The quantitative analyses revealed significant increases in the expression of 4 microRNAs (miR-221-3p, miR-222-3p, miR-455-3p, and miR-195a-5p) and decreases of 2 microRNAs (miR-122-5p and miR-7a-1-5p) during hibernation. RNA sequencing and in silico target prediction regarding 3 upregulated microRNAs (miR-221-3p, miR-222-3p and miR-455-3p) found 13 target mRNAs with significantly decreased expression during hibernation. The transfection of microRNA mimics into cells showed that miR-222 and miR-455 reduced solute carrier family 16 member 4 ( SLC16A4 ) and fatty acid synthase (FASN ) mRNA expression, respectively. Our results suggest that the increased levels of hepatic miRNA during hibernation (miR-222-3p and miR-455-3p) negatively regulate the expression of targeted genes predicted to be involved in the transport of energy source and de novo fatty acid synthesis, is consistent with a regulatory role of these miRNAs in energy metabolism in hibernating black bears.